Senseless Women - Wallman, Sarah Harris (Book collections on Project MUSE., 2020)
"Exploring the darker side of optimism, Sarah Harris Wallman's debut collection shows women attempting to build durable havens from reality, struggling to keep relationships intact, and reinventing themselves. A lonely music teacher at a Nashville Christian academy awaits the miracle of love; a Jane Doe recalls the affair that sustained, and ended, her; a new mother brings life into the world during a bleak election party; young girls are exploited by a nightclub owner in death, as in life. Alone or in weird sisterhood, some of these women are senseless because they refuse to feel, others because they've been deprived of stimuli and attention. As these twelve stories prove, there's no sensible way to fall in love, raise children, or escape. This is Senseless Women"--